Application of small punch creep testing to a thermally sprayed CoNiCrAlY bond coat - Chen, H.; Hyde, T.H.; Voisey, K.T.; McCartney, D.G. (Elsevier, 2013)
High velocity oxy-fuel thermal spraying was used to prepare free-standing CoNiCrAlY (Co–31.7% Ni–20.8% Cr–8.1% Al–0.5% Y (wt%)) bond coat alloy samples approximately 0.5 mm thick. Creep tests were conducted at 750 °C on these samples using a small punch (SP) creep test method. The samples were characterised before and after creep testing using scanning electron microscopy with electron backscatter diffraction (EBSD). EBSD revealed a two phase fcc γ-Ni and bcc B2 β-NiAl microstructure with grain sizes ~1–2 μm for both phases, which did not change significantly following testing. The constant temperature SP test data were characterised by a minimum creep strain rate, View the MathML source, and a total time to failure, tf, at different applied stresses. The data are fitted to conventional power law equations with a stress exponent for creep close to 8 in the Norton power law and between 7 and 10 in the Monkman–Grant creep rupture law. Creep rupture was predominantly due to creep cavitation voids nucleating at both the γ–β interphase boundaries and the γ–γ grain boundaries leading to final failure by void linkage. However, rupture life was influenced by the quantity of oxide entrained in the coating during the spray deposition process.